Um estudo sobre a intervenção com o professor de educação física para a inclusão educacional do aluno com deficiência visual - Fiorini, Maria Luiza Salzani [UNESP]; Nabeiro, Marli [UNESP] (My University, 2013)
It was aimed to identify how the physical education teachers worked to include a student with visual impairment; intervene with the teacher from the identified necessities and assess the intervention. Data were collected in three stages: 1) Weekly monitoring and filming the classes, 2) intervention by the reflection of videos coming from the previous step and suggesting new actions, 3) development of filming for evaluating the intervention. Before the intervention, it was identified that the explanation of the activities happened collectively. It was held the physical help as the first form of instruction, the student with visual impairment participation occurred depending on the company of a classmate who held hands and did the activities together. Along the intervention it was reflected about the structure of the classes, the ways of explanation of the activities and the strategies and the resources to assure an enjoyable participation of students with visual impairments. The training of peer tutors was a strategy used. After the intervention it was identified in the classroom the assistance of the trained peer tutors; the maintenance of oral explanation and demonstration, though, the first way to explanation for the student with visual impairment started to be the oral tip.

Objetivou-se identificar como o professor de Educação Física atuava para incluir um aluno com deficiência visual; intervir junto ao professor a partir das necessidades identificadas e, avaliar a intervenção. Os dados foram coletados em três etapas: 1) acompanhamento semanal e filmagem das aulas; 2)intervenção por meio da reflexão dos vídeos advindos da etapa anterior e sugestão de novas ações; 3) realização de filmagens para avaliar a intervenção. Antes da intervenção identificou-se que a explicação das atividades era coletiva, com instrução e demonstração, entretanto, para o aluno com deficiência visual, era realizada a ajuda física como primeira forma de instrução; a participação do aluno com deficiência visual ocorria em função da companhia de um colega da turma que, de mãos dadas, executavam conjuntamente as atividades. Na intervenção refletiu-se sobre estrutura da aula, formas de explicação das atividades e, estratégias e recursos para garantir uma participação prazerosa do aluno com deficiência visual. O treinamento de colegas tutores foi uma das estratégias. Após a intervenção foi identificado, nas aulas, o auxílio dos colegas tutores treinados; manutenção da explicação verbal e da demonstração, porém, a primeira forma de explicação, para o aluno com deficiência visual passou a ser a dica verbal.
A study of the intervention with the physical education teacher for inclusion of students with visual impairment
Keywords: Physical education; Special education; Training of teachers; Educação física; Educação especial; Formação de professores